Apoptosis and transcriptome analyses of Crandell Reese feline kidney cells following infection with feline infectious peritonitis virus strain WSU 79- 1146 - Shuid, Ahmad Naqib (2013)
Feline infectious peritonitis (FIP) is a fatal, progressive and immune-augmented disease of cats caused by feline coronavirus (FCoV) infection. FIP pathology is characterized typically by severe systemic inflammatory damage of serosal membranes and widespread pyogranulomatous lesions. In addition, apoptosis of T-cells and changes in cytokine expression are observed in end-stage FIP. Despite of over 40 years of research, the mechanism of IPFV-induced disease and immunity remains unclear. Currently there is no diagnostic protocol that can discriminate the avirulent FCoV from FIPV and there is no effective treatment or vaccine available. In addition, the molecular pathogenesis of feline infectious peritonitis (FIPV) induced disease is poorly characterized. RNA sequencing using next-generation sequencing (NGS) technology allows better quantification of the expression levels of the entire transcriptome with a high dynamic range. In the present study, analysis on mode of cell death of uninfected and FIPV infected CRFK was performed at different time points and followed by a comparative transcriptome analysis of FIPV strain 79 – 1146 infected Crandell Reese feline kidney (CRFK) cells at 9 hours post-infection was performed using Illumina Genome Analyzer. Sequence reads were assembled and analyzed using CLC bio Genomic Workbench software to generate RNA-seq library. Approximately 98 million sequenced reads were obtained from both uninfected and infected samples. A gene transfer format (GTF) annotated 2X whole genome shotgun sequencing of Felis catus from www.ensembl.org were used as reference in the RNA-seq analysis. Gene expression was estimated by calculating read density as ‘reads per kilobase of exon model per million mapped reads’ (RPKM) whilst, Gene Ontology analysis was performed to establish the function of differentially expressed genes among samples. From a total of 19046 annotated reference genes, 11124 genes were expressed in untreated and 11453 genes were expressed in infected CRFK cells. CLC bio Genomic Workbench further isolated a total of 1837 normalized differentially expressed genes (DEG) using Kal’s test comparison feature set up at a false discovery rate (FDR) less than 0.05 (FDR <0.05) with increased and decreased in proportion fold change more or less than 2 (-2 > X > 2). Generated up-regulated and down-regulated DEGs were then subjected to bioinformatic analysis separately using Database for Annotation and Integrated Discovery (DAVID) which clustered 1403 DEGs from a total of 1837 normalized DEGs into 135 clusters of up-regulated and 170 clusters of down-regulated DEGs. Genes that belong to apoptosis, cell cycle and immune response clusters, together with the genes that were over- and under-expressed (-∞ > X > ∞) and other genes that were speculated of importance in FIPV immunopathology were selected for further in silico analysis. From a total of 57 speculated DEGs in the cell cycle cluster, 20 genes (Gtse1, Anapc11, Uba7, Nek6, Mcm8, Ptp4a1, Eif4ebp1, Magoh, Ern2, Fbxw4, Cyld, Rad51, Nhej1, Neil, Nthl1, Apitd1, Htra2, Cdk2, Smad3 and Smarcb1) were hypothesized to be important in deregulation of cell cycle during FIPV infection. From the genes that involved in deregulation of apoptosis, at least 8 speculated pro-apoptotic genes (Arghdia, Htra2, Cidec, Nox5, Bnip3l, Ptprf, Smad3 and Traip) and 6 speculated anti-apoptotic genes (Bag4, Ywhaz, Cryab, Adam9, F3, and Api5l1) were speculated to be involved in deregulation of FIPV-induced apoptosis. Meanwhile, 9 deregulated genes (Poll, Sbno2, Polr3b, F3, Smad3, Shb, Nod2, Pdgfb and Fcn3) which might be involved in deregulating immune response. Apart from that, other genes that were not grouped under the immune response cluster such as Raf1, Nfatc2 and Chp2 were also hypothesized to play important role in immune responses against FIPV since previous studies showed that these genes deregulate T cells, B cells and natural killer (NK) cells activity. From a total of 5 over- and 8 under-expressed genes (-∞ > X > ∞), only 6 genes with known functions such as cytokine-chemokine genes (CCL-4 and G-CSF), heavy metals and glucocorticoids transcriptionally regulated gene (Mt2a), a nuclear transcription factor (Ankrd1), clathrin associated adaptor genes (Ap1s2) and an integral membrane protein encoding gene (Tgoln2) were identified. Furthermore, the most unique DEG in this study was Smad3 as it was found to be deregulated in all of the selected clusters. SMAD 3 is an intracellular signal transducer and transcriptional modulator as it was found to be deregulated in all the three chosen clusters. In conclusion, it can be suggested that apoptosis and not necrosis is the mode of cell death in FIPV infected CRFK cells while in transcriptomic study, from a total of 1837 significantly DEGs, a total of 57 DEGs were found in cell cycle cluster, 41 DEGs were found in apoptosis clusters and 16 DEGs were found in immune system cluster. Further in vitro and in vivo studies are required to evaluate the involvement of these genes in FIPV immunopathology.